2020
DOI: 10.1021/acs.jpcc.0c04158
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Transport of Water and Ions through Graphene Nanochannels

Abstract: Water and ion transport through graphene nanochannels has attracted considerable attention thanks to the possibility of dimensional control of the channel sizes down to a single atomic layer. Using molecular dynamics simulations, we systematically analyzed the coupled transport of water and ions in the solutions of LiCl, NaCl, and KCl salts as a function of channel sizes, applied electric fields, and salt concentrations. A universal order of ion flux is found with K + > Cl − > Na + ≈ Li + , and the K + flux is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…For D/d = 1.5, the Na + flux is very small, and the negative flux becomes larger (see Figure 2a inset), whose values are not sensitive to the positive field strength. This is similar to previous experiments 35,36 and simulations, 11 where the ion flux is nearly zero for single-layer graphene channels. This abnormal result can be attributed to the dehydration of Na + .…”
Section: ■ Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…For D/d = 1.5, the Na + flux is very small, and the negative flux becomes larger (see Figure 2a inset), whose values are not sensitive to the positive field strength. This is similar to previous experiments 35,36 and simulations, 11 where the ion flux is nearly zero for single-layer graphene channels. This abnormal result can be attributed to the dehydration of Na + .…”
Section: ■ Introductionsupporting
confidence: 92%
“…Actually, the ion hydration structures are highly relevant to their dynamics. For example, a recent experimental study found that on a solid surface, the migration of Na + strongly depends on its hydration number, while the dehydration plays a crucial role in determining the ion transport and selectivity in nanochannels. ,, For the present asymmetric graphene channel, the ion dehydration is simply due to the steric exclusion, where the ion hydration number changes differently in positive and negative directions. As seen in Figure a, under the positive E = 0.5 V/nm, Na + moves from the base to tip, where its hydration number decreases in a wide region for the case of D / d = 1.5.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…To the best of our knowledge, previous studies mostly focused on nanocone channels for ionic transport, 10,[18][19][20][21] while recent experiments demonstrate unique transport behaviors in two-dimensional graphene channels. [22][23][24][25] In particular, inside such graphene channels, ions will have two-dimensional hydration structures 26 and exhibit ultrahigh diffusivity, 27 where the ions also can assemble into monolayer crystal structures 28 or elongated clusters under electric fields. 15 Furthermore, when the graphene channels are asymmetric, the water and ions exhibit specific rectification correlation in electric fields; 29 however, the desalination behaviors in such asymmetric graphene channels are still unexplored.…”
Section: Introductionmentioning
confidence: 99%